THE USE OF ROLE PLAY TOWARD THE IMPROVEMENT OF THE FIRST-SEMESTER STUDENTS’ SPEAKING SKILLS IN BUSINESS ADMINISTRATION MAJOR AT MANADO STATE POLYTECHNIC - Reski Amalia. S (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2023)
The objective of this research was to find out the effectiveness of Role play toward the improvement of students speaking skills majoring in Business Administration at Manado State Polytechnic. This research employed a quasi-experimental namely non-equivalent control group design with pre-test and post-test. There were two variables in this research; the independent variable (role play) and the dependent variable (students’ speaking skills). The population of this research was first-semester students majoring in Business Administration which consist of 55 students. The sample of this research consisted of 40 students taken by using a purposive sampling technique, 20 students from 1AB1 as the experimental class and 20 students from 1AB2 as the control class. Pre-test and post-test were used as the instrument in this research. The data explained that there was a significant difference between the students’ post-test in the experimental class and post-test in the control class. The mean score of the post-test (77) in the experimental class was higher than the mean score on the post-test (65) in the control class. The standard deviation on the post-test is (10,43) in the experimental class and the standard deviation of the post-test in the control class is (11,12). Based on the finding and discussion of the research, the researcher concluded that role play was effective to improve students’ speaking skills.